Edukasi Pencegahan Virus Covid-19 Bagi Ibu yang Memiliki Balita di Desa Kutagandok Melalui Zoom Meeting - Febi Fauziyah; Syifaul Fuada (Politeknik Negeri Madiun, 2021)
Kutagandok Village is located in Kutaluya District, Karawang Regency, West Java which has found positive COVID-19 people. In this village, several mothers who have toddlers are very worried about the news of the Covid-19 virus. With its very fast spread, they are worried that their toddlers will be suspected of the Covid-19 virus. Therefore, we provided an education program on preventing the Covid-19 virus among mothers in the village through a webinar. It is hoped that the mothers targeted for this program can do the best prevention for themselves and their toddlers from the spread of the Covid-19 virus. The webinar is carried out in the Zoom Meeting platform. Before, the webinar program is promoted through pamphlets sent through WhatsApp messages to mothers who will participate in the webinar. The target of the webinar program is 4 out of 10 invited mothers, which will be held on 28-November- 2020. The activity lasts for 40 minutes, from 14.00-14.40 WIB. The webinar results can answer mothers’ concerns about the spread of the Covid-19 virus. Thus, in their daily lives, they can implement several efforts to prevent the Covid-19 virus. This webinar received a positive response from the participants to run well and provide useful results.